ANALISIS DAN PERANCANGAN USER INTERFACE MARKETPLACE HIDROPONIK BERBASIS LEAN UX (STUDI KASUS: PETANI HIDROPONIK DI KABUPATEN BANYUWANGI) - Anshor, Mohamad Mujahidin; Sagirani, Tri; Amelia, Tan (Jurnal Sistem Informasi Universitas Dinamika, 2020)
The limited market segment of hydroponic products makes it difficult for hydroponic farmers to develop their businesses. The impact of slow sales and limited marketing of products from farmers can cause a decline in the competitiveness of other products and the long term can affect the farmer's economy. With a marketplace that sells hydroponic products, it is expected that hydroponic farmers can sell their products online. In building a marketplace, one thing that is of concern is the ease of utilizing the marketplace, this means paying special attention to the design stage of the user interface or user interface of the marketplace. User Interface has an important role in building an information system. Lean UX was chosen in building the user interface because it is one of the methods in designing interface designs to meet the needs of users with frequent learning and involving users as early as possible so that they can meet the needs of users quickly. There are 4 stages in the Lean UX method namely Declare Assumption , Create an MVP, Run an Experiment, and Feedback & Research. The results of tests that have been done to 32 respondents using usability testing show that designs that have been made get an average value of 78.9%, acceptable with grade B and obtain range good, which means the design can be accepted by users well.